2017
DOI: 10.1111/eea.12545
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoids follow herbivorous insects to a novel host plant, generalist predators less so

Abstract: The ‘enemy‐free space’ hypothesis predicts that herbivorous insects can escape their natural enemies by switching to a novel host plant, with consequences for the evolution of host plant specialisation. However, if natural enemies follow herbivores to their novel host plants, enemy‐free space may only be temporary. We tested this by studying the colonisation of the introduced tree Eucalyptus grandis (Hill) Maiden (Myrtaceae) by insects in Brazil, where various species of herbivores have added eucalyptus to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…While optimization of herbivore performance, as measured by bitrophic indices focusing solely on the herbivore–plant interaction, often fails to explain patterns of host plant use (Forister et al, 2009; Mason et al, 2011), persistence on novel host plants involves an array of ecological, behavioral, and physiological factors beyond suitability for development (Forister & Wilson, 2013; Mason, 2016). In particular, herbivore interactions with natural enemies, including predators (Grosman et al, 2017; Murphy, 2004), parasitoids (Fortuna et al, 2013; Harvey & Fortuna, 2012), and pathogens (Cory & Hoover, 2006; Shikano, 2017) can differ substantially between native and exotic host plant species. As these interactions comprise a major source of mortality for insect herbivores (Hawkins et al, 1997), exploitation of enemy‐free or enemy‐reduced space may constitute an important driver of host range evolution (Bernays & Graham, 1988; Jeffries & Lawton, 1984; Singer & Stireman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While optimization of herbivore performance, as measured by bitrophic indices focusing solely on the herbivore–plant interaction, often fails to explain patterns of host plant use (Forister et al, 2009; Mason et al, 2011), persistence on novel host plants involves an array of ecological, behavioral, and physiological factors beyond suitability for development (Forister & Wilson, 2013; Mason, 2016). In particular, herbivore interactions with natural enemies, including predators (Grosman et al, 2017; Murphy, 2004), parasitoids (Fortuna et al, 2013; Harvey & Fortuna, 2012), and pathogens (Cory & Hoover, 2006; Shikano, 2017) can differ substantially between native and exotic host plant species. As these interactions comprise a major source of mortality for insect herbivores (Hawkins et al, 1997), exploitation of enemy‐free or enemy‐reduced space may constitute an important driver of host range evolution (Bernays & Graham, 1988; Jeffries & Lawton, 1984; Singer & Stireman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…If a phytophagous species uses those new allelochemicals to defend against parasitoids and predators (compare Harvey et al, 2010; Bezemer et al, 2014), through sequestration (Beran & Petschenka, 2022), the efficiency of its natural enemies may be affected. This could have suppressed or released effects on the herbivore, depending on whether the higher trophic levels have advantages or disadvantages from the novel host traits (compare Harvey et al, 2010; Grosman et al, 2017), and may lead to further evolutionary responses between the host and the natural enemy. Moreover, an altered host plant range in herbivorous pollinators such as within Lepidoptera may affect plant–insect mutualisms and their ecosystem service capacity.…”
Section: Ecological Consequences Of Pesticide Resistance Developmentmentioning
confidence: 99%
“…In our research, generalists and specialists were represented by G. quinquepunctata and A. brevicollis coryletorum, respectively. According to Grosman et al (Grosman et al, 2017) predators follow herbivorous insects to a new host plant slower and to a lesser extent than do parasites. They also concluded that predator movement is a matter of time and in the long run, predators will also adapt to hunting herbivores on a new host plant.…”
Section: Relationship Between Leaf Damage By Insect Folivores and DImentioning
confidence: 99%